Analytical approximate solution of higher order boundary value problems via variational iteration method - Ahmad, Jamshad; Hamid, Zobia (BIBECHANA, 2017)
In this paper, application of variational iteration method has been successfully extended to obtain approximate solutions of some higher order boundary value problems. We emphasize the power of the method by testing three different mathematical models of distinct orders. The results are obtained by using only little iteration.  BIBECHANA 15 (2018) 37-42